Strength Characteristics of DMJ Piles Based on Indoor Tests - Hongzhi Yue; Yuhe Zhang; Yu Rong; Weizhe Feng; Yang Wang; Lin Zhao; Songtao Wang; Ruosong Ding; Fan Yang; Zhanyong Yao; Kai Yao (Infrastructures, 2024)
The Deep Cement Mixing Integrated Drilling, Mixing and Jetting (DMJ) method represents a novel approach to the construction of slurry piles in the Yellow River Floodplain, offering the potential to enhance the quality of these structures. In order to investigate the pile strength and its distribution characteristics under different conditions, an unconfined compressive strength test was conducted on DMJ pile core samples. The Kolmogorov-Smirnov (K-S) test was employed to evaluate the normal distribution characteristics of the strength, and the fluctuation of the pile strength was evaluated by the autocorrelation function method to elucidate the distribution characteristics. Moreover, a resistivity non-destructive test was conducted to ascertain the correlation between strength and resistivity and to perform supplementary strength testing. The distribution of the pile body strength is normal at the 5% level of significance. A clear correlation was observed between the strength of the pile core and depth, while the correlation between the strength of the pile outer side and depth was less pronounced. Additionally, a positive linear correlation was observed between resistivity and strength, which can be used to evaluate the strength of DMJ piles.